2017
DOI: 10.1016/j.jallcom.2017.03.143
|View full text |Cite
|
Sign up to set email alerts
|

Giant pyroelectric properties in La and Ta co-doped lead-free 0.94Na 0.5 Bi 0.5 TiO 3 -0.06BaTiO 3 ceramics

Abstract: La and Ta co-doped Lead-free 0.94NBT-0.06BT ceramics were synthesized by a conventional solid-state route. The compositions remain at a morphotropic phase boundary. The depolarization temperature (Td) decreased with increasing doping contents. The room temperature (RT) pyroelectric coefficient (p) was highly enhanced compared with undoped material (3.15 x10-4 C.m-2 .°C-1) and reached 12.9 x10-4 C.m-2 .°C-1 , whereas, at Td, 58.6 x10-4 C.m-2 .°C-1 could be obtained rather than 23.9 x10-4 C.m-2 .°C-1 for undoped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“… Mn‐doped 0.97K 0.5 Na 0.5 NbO 3 –0.03(Bi 0.5 K 0.5 )TiO 3 , (K 0.5 Na 0.5 ) 0.96 Li 0.04 ](Nb 0.84 Ta 0.1 Sb 0.06 )O 3 , Ca 0.2 Sr 0.1 Ba 0.7 Nb 2 O 6 , 0.6(Ba 0.9 Ca 0.1 )TiO 3 –0.4Ba(Sn 0.2 Ti 0.8 )O 3 , 0.93(Bi 0.5 Na 0.5 )TiO 3 –0.07Ba(Ti 0.945 Zr 0.055 )O 3 , 0.93(Bi 0.5 Na 0.5 )TiO 3 –0.07Ba(Ti 0.945 Zr 0.055 )O 3 –0.125 mol.% Mn, 0.94(Bi 0.5 Na 0.5 )TiO 3 –0.06BaTiO 3 –0.005La, 0.005La–0.94(Bi 0.5 Na 0.5 )TiO 3 –0.06BaTiO 3 –0.002Ta, 0.71(Bi 0.5 Na 0.5 )TiO 3 –0.065BaTiO 3 –0.22SrTiO 3 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Mn‐doped 0.97K 0.5 Na 0.5 NbO 3 –0.03(Bi 0.5 K 0.5 )TiO 3 , (K 0.5 Na 0.5 ) 0.96 Li 0.04 ](Nb 0.84 Ta 0.1 Sb 0.06 )O 3 , Ca 0.2 Sr 0.1 Ba 0.7 Nb 2 O 6 , 0.6(Ba 0.9 Ca 0.1 )TiO 3 –0.4Ba(Sn 0.2 Ti 0.8 )O 3 , 0.93(Bi 0.5 Na 0.5 )TiO 3 –0.07Ba(Ti 0.945 Zr 0.055 )O 3 , 0.93(Bi 0.5 Na 0.5 )TiO 3 –0.07Ba(Ti 0.945 Zr 0.055 )O 3 –0.125 mol.% Mn, 0.94(Bi 0.5 Na 0.5 )TiO 3 –0.06BaTiO 3 –0.005La, 0.005La–0.94(Bi 0.5 Na 0.5 )TiO 3 –0.06BaTiO 3 –0.002Ta, 0.71(Bi 0.5 Na 0.5 )TiO 3 –0.065BaTiO 3 –0.22SrTiO 3 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, a rather high p of 7.42 × 10 −8 Ccm −2 K −1 in BNT–BT ceramics was achieved by Balakt et al through La doping . Moreover, Ta doping further improved the p of this composition to 12.9 × 10 −8 Ccm −2 K −1 , which showed one order of magnitude higher than other lead‐containing and lead‐free ceramics. However, the depolarization temperature T d was rather low (74°C for La doped BNT–BT and 54.9°C for Ta further doping, respectively), resulting in poor thermal stability, as manifested in a sharp increase of p at elevated temperature.…”
Section: Introductionmentioning
confidence: 98%
“…Pyroelectric materials are attracting significant attention because they play an important role in infrared detectors, sensors, thermal imaging, and energy harvesting applications . Moreover, there is a close relationship between pyroelectric coefficient and electrocaloric effect based on the thermodynamic Maxwell relation .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exploration and development of a novel high performance lead‐free pyroelectric material are highly desirable and urgently needed. In recent years, palpable progress has been made for the investigation of lead‐free pyroelectric materials, such as (Bi 0.5 Na 0.5 )TiO 3 ‐based, (K 0.5 Na 0.5 )NbO 3 ‐based, (Sr 1‐ x Ba x )Nb 2 O 6 ‐based, and BaTiO 3 ‐based materials . For example, Balakt et al observed significantly enhanced pyroelectric coefficient ( p , 12.9 × 10 −8 C cm −2 K −1 ) in La/Ta co‐doped 0.94Na 0.5 Bi 0.5 TiO 3 ‐0.06BaTiO 3 lead‐free ceramics .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation